2019
DOI: 10.1001/jamafacial.2018.1737
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tranexamic Acid in Reducing Intraoperative Blood Loss and Postoperative Edema and Ecchymosis in Primary Elective Rhinoplasty

Abstract: IMPORTANCE Blood loss from surgical procedures is a major issue worldwide as the demand for blood products is increasing. Tranexamic acid is an antifibrinolytic agent commonly used to reduce intraoperative blood loss.OBJECTIVE To systematically examine the role of tranexamic acid in reducing intraoperative blood loss and postoperative edema and ecchymosis among patients undergoing primary elective rhinoplasty.DATA SOURCES A systematic review and meta-analysis was undertaken in an academic medical setting using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
0
28
0
1
Order By: Relevance
“…We put forward that TXA due to its low cost, its safety in use, and its effectiveness in results [5,20,33] should be considered a fundamental tool in the prevention of complications in rhytidoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…We put forward that TXA due to its low cost, its safety in use, and its effectiveness in results [5,20,33] should be considered a fundamental tool in the prevention of complications in rhytidoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various points of between-study heterogeneity, e.g., local infiltration of vasoconstrictors (infiltrated [16] vs. not infiltrated [15]), method of TXA administration (oral [15,17] vs. IV [14,16]), surgical approach (open [14,17] vs. close [16]), and performance of septoplasty (performed [16,17] vs. not mentioned [14,15]), most of the previous studies unanimously indicated TXA to be effective in reducing intraoperative blood loss. In the most recent meta-analysis of the evidence in 2019, McGuire et al stated that high-quality evidence is in support of TXA efficacy, not only in reducing intraoperative bleeding, but also in reducing postoperative edema and ecchymosis [18]. However, from a statistician's point of view, the asymmetry of the funnel plot of the included studies in this meta-analysis [14][15][16][17] (figure 2, Egger's test P = 0.071, significant at 90% level 1 ), may be pointing at possible missing results, and indicating a need for more evidence in this regard; a statement supported by the current study and a recent trial from Avci, which in line with the current study, showed a statistically insignificant decrease in blood loss during rhinoplasty following TXA administration versus controls [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses of previous evidence have suggested TXA to be significantly effective in reducing blood loss, increasing surgical field quality, and reducing postoperative ecchymosis and edema during rhinoplasty [18][19][20]. However, most of the previously conducted studies either enrolled small sample sizes, or had a wide range of objectives, rendering them to reduced precision.…”
Section: Introduction Background and Objectivesmentioning
confidence: 99%
“…The potential therapeutic benefit of TXA in elective rhinoplasty has only recently been investigated. There exist 2 similar meta-analyses 28,29 evaluating the findings of five randomised control trials 30e34 (Table 3). The main outcomes assessed included intraoperative blood loss, post-operative swelling and postoperative periorbital ecchymosis.…”
Section: Rhinoplastymentioning
confidence: 99%